Teacher Understanding and Application of Cognitive–Behavioural Approaches for Students With Autism Spectrum Disorder and Intellectual Disability. Issue 1 (7th February 2019) - Ho, Betty P. V.; Stephenson, Jennifer; Carter, Mark
Abstract: This study provides an in-depth examination of the understanding and implementation of cognitive–behavioural approaches (CBA) by Australian teachers of students with both autism spectrum disorder and intellectual disability. Semistructured interviews were completed with 13 New South Wales teachers and several themes emerged. Interviewed teachers appeared to have limited knowledge about CBA; their description of the application of CBA and their reported practices included few features specific and unique to CBA. They primarily perceived CBA as a tool for behaviour management; addressing emotion was a theme but addressing cognition was not a salient feature of their practice. Most teachers seemed unaware of the potential of CBA in fostering generalisation or maintenance, and important student characteristics appeared to be seldom considered in teacher planning of their CBA programs. Directions for enhancing teacher knowledge and supporting their practice of CBA are suggested.